Upaya Meningkatkan Minat Menghafal Hadits Melalui Penerapan Metode Gerakan Pada Anak RA Al-Hikmah Tanjungsari - Lulu Eljannah; Siti Fatimah; Fuad Hasyim (IAINU Kebumen, 2023)
This study aims to determine the increase in children's memory in memorizing Hadith through the Movement Method at RA Al-Hikmah. This type of research is Classroom Action Research (CAR), which will be conducted from April 2023 to May 2023. This research consists of two cycles with four main activities in each cycle, namely planning, action, observation, reflection. Data were analyzed using quantitative data. The subjects in this study were the children of RA Al-Hikmah Tanjungsari. Totaling 30 children. The data collection technique used is the observation technique. Observations were made directly to see the implementation of the hadith memorization program at RA Al-HIKMAH Tanjungsari. The results of the analysis showed an increase, namely in the first cycle there were 60% of students getting an increased pass score, in the second cycle there were 90% of students getting a complete score. So it can be concluded that the movement method can increase interest in memorizing hadith in RA Al-Hikmah Tanjungsari's children.